Railway Rates and Joint Cost - Pigou, A. C.; Taussig, F. W. (Quarterly Journal of Economics, 1913)
Journal Article Railway Rates and Joint Cost Get access A. C. Pigou, A. C. Pigou King's College, Cambridge, England Search for other works by this author on: Oxford Academic Google Scholar F. W. Taussig F. W. Taussig Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 27, Issue 3, May 1913, Pages 535–538, https://doi.org/10.2307/1883378 Published: 01 May 1913